The Rap80-BRCC36 de-ubiquitinating enzyme complex antagonizes RNF8-Ubc13-dependent ubiquitination events at DNA double strand breaks - Shao, Genze (National Academy of Sciences, 2009)
DNA double strand breaks (DSBs) initiate reversible cellular checkpoint and repair activities. Whereas many of the activating events at DSBs have recently been elucidated, the mechanisms used to terminate responses at these sites are largely undefined. Here we report a pathway required to reverse RNF8-Ubc13 dependent ubiquitination events on chromatin flanking DSBs. Inhibition of the Rap80-BRCC36 de-ubiquitinating enzyme complex partially restored DSB-associated ubiquitin levels following RNF8 knockdown or proteasome inhibition. Similarly, BRCC36 knockdown or expression of a BRCC36 de-ubiquitinating enzyme-inactive mutant rescued both 53BP1 recruitment to DSBs and ionizing radiation-induced γH2AX ubiquitination following RNF8 depletion, and mitigated ionizing radiation sensitivity resulting from RNF8 deficiency. Thus, concomitant and opposing RNF8-Ubc13 ubiquitin ligase and Rap80-BRCC36 ubiquitin hydrolysis activities are responsible for determining steady-state ubiquitin levels at DNA DSBs. These findings reveal a Rap80-BRCC36 dependent pathway that is required for appropriate DSB recruitment and repair responses.